Pengendalian Risiko K3 pada Teknisi Unit IOAN PT Telkom Akses dengan menggunakan Metode Job Safety Analysis - 10070217046, Annisa Arsya Effeli; Aviasti; Nur Rahman As’ad (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. IOAN is a division of the PT Telkom Access work unit tasked with handling IndiHome disruptions. Very high level of mobilization causes the level of work accidents experienced by technicians to be very high. Throughout 2021, there were 67 cases of work accidents. This research aims to determine the stages of IOAN work that have a risk of work accidents and determine risk control using Job Safety Analysis (JSA) and Risk Analysis AS/NZS 4360:2004. Research provides the results of 6 work steps with 16 potential hazards. Recommendations are given to the very high and priority 1 categories because these categories are related to death and require control as soon as possible. Recommendations for improvement include safety riding training provided every 3 months in the warehouse, 2-wheeled motorbike checks carried out every day, reminders of OSHMS SOPs by warehouse officers every day, warehouse officers carrying out daily PPE checklists, K3 socialization given every month, and In the warehouse area, tools and work facilities are checked every month, and renewals are carried out for tools and work facilities that are no longer suitable, safety cones are checked regularly, and drinking water is provided in bottled form, so it is more practical. Abstrak. IOAN merupakan divisi dari unit kerja PT Telkom Akses yang bertugas menangani gangguan IndiHome. Tingkat mobilisasi yang sangat tinggi menyebabkan tingkat kecelakaan kerja yang dialami oleh teknisi sangat tinggi. Sepanjang tahun 2021 terjadi 67 kasus kecelakaan kerja. Penelitian ini bertujuan untuk mengetahui tahapan pekerjaan IOAN yang memiliki risiko kecelakaan kerja, dan mengetahui pengendalian risiko dengan menggunakan Job Safety Analysis (JSA) dan Analisis Risiko AS/NZS 4360:2004. Penelitian memberikan hasil 6 langkah pekerjaan dengan 16 potensi bahaya. Rekomendasi diberikan pada kategori very high dan priority 1 karena kategori tersebut berkaitan dengan kematian dan memerlukan pengendalian sesegera mungkin. Rekomendasi perbaikan yang diberikan di antaranya pelatihan safety riding diberikan setiap 3 bulan di setiap warehouse, pengecekan kendaraan motor roda 2 dilakukan setiap hari, reminding SOP SMK3 oleh petugas warehouse setiap hari, petugas warehouse melakukan daily checklist APD, sosialisasi K3 diberikan setiap bulan dan di area warehouse, pengecekan alat dan sarana kerja dilakukan setiap bulan dan dilakukan renewal untuk alat dan sarana kerja yang sudah tidak layak, pengecekan safety cone secara rutin, air minum disediakan dalam bentuk botol kemasan sehingga lebih praktis.